Assessing Approaches To Changing Road Safety Behaviours Of Commercial Drivers In Ho Municipality, Ghana. - Abimah, L. (University of Ghana, 2013)
Ghana has considerable problems with road safety which manifest in the numerous incidences of road accidents. In the past, road safety management was characterized by dispersed, uncoordinated, and insufficiently resourced institutional units performing isolated single functions by individual departments within the Ministry of Roads and Transport. Currently, the National Road Safety Commission (NRSC), Police MTTU and DVLA together with other stakeholder organizations were mandated to address the incidence of unacceptably high levels of road traffic crashes in the country by enforcing and regulating road traffic rules and regulations. Yet, due to the ever-increasing vehicular fleet in the country, the notoriously bad attitude of road users and the weak enforcement of traffic rules, the absolute number of deaths and injuries still fluctuate within unacceptable ranges. Additionally, there appeared to be legislative, institutional, administrative and procedural inadequacies which were also aggravated by problems of inadequate logistics and funding for road safety activities. The study, therefore sought to assess the effectiveness of the approaches used to change road safety behaviour among commercial drivers in Ho Municipality. In all, a sample of 103 respondents was used for the study. The research used the descriptive analytic survey design. An interview schedule, focus group discussion, in-depth interview, observation and document review were the main data gathering instruments used in collecting data. Face-to-face interviews were conducted on 78 commercial drivers who were simple randomly sampled. Two focus group discussions were held for 8 commercial drivers and 6 driver union leaders. In-depth interviews were held with one regional head and some frontline staffs of the police MTTU, DVLA and the NRSC who were purposively sampled. Observation method was also used together with the in-depth interview to collect data from the DVLA. Document review was used to collect information on road safety legislation. The results of the study revealed that the commercial drivers met the stipulated minimum educational requirement but their educational levels were low. Learning by apprenticeship was the main mode of training for commercial drivers and some drivers still obtained and renewed their licenses and road use certificates through agents. The commercial drivers had poor knowledge on road traffic rules and regulations, but they perceived the police MTTU and the DVLA to be effective in regulating road traffic rules. The majority of the commercial drivers have not had any incentive or reward and most of them have not attended any driver education or training since they started driving. Ghana has a comprehensive legislation on road safety; the police MTTU enforced road traffic rules; the DVLA ensured best practices of licensing drivers and vehicles and the NRSC provided leadership in the development and implementation of measures that will reduce road traffic accident fatalities. Some challenges faced by commercial drivers included bad nature of the roads, poor signing and markings and numerous speed humps; and the commercial drivers do not have professional education and training opportunities. Legislation on road safety spelt out the condition under which a person would be said to have committed a road traffic offence. The police MTTU ensured safety on the roads through road checks to ensure compliance with road safety rules and regulations and the provision of road safety education. The DVLA regulated drivers and enforced road traffic rules and regulations. Reinforcement of drivers included incentives and rewards and the NRSC undertook nationwide planning, development and implementation of road safety programmes and activities and road safety education. Some of the challenges faced by the approaches to change driver behaviour included outdated road safety regulations; lack of adherence to most of the existing Acts, regulations and by-laws; and absence of a regulatory authority. The Police MTTU, DVLA and NRSC were challenged by limited logistics and personnel to carry out effective enforcement, regulation and education on road safety. There was political interference in the operations of the police MTTU, DVLA and NRSC in the discharge of their duties. Based on the findings of the study the following recommendations were made: - Encouraging cooperation between driving schools and the informal driver training systems in the training of learner drivers may be beneficial in increasing the quality of instruction and the breadth and depth of learner driver experience. - Driver education and training programmes should be included in the Transport Unions’ and companies’ planning process so that the necessary funding and other resources are made available to enable drivers to access timely and appropriate training. - There should be periodic review of Road Traffic Act and regulations since some of the road traffic laws were based on assumptions about outdated automotive technology and have not been reviewed as technology improved. - Driving incentive programmes can be used to motivate commercial drivers to improve their performance. - The capacity and resources of the police MTTU, DVLA and NRSC should be improved sufficiently to ensure effective and efficient enforcement and regulation of road traffic rules.
Thesis (MPhil) - University of Ghana, 2013
Keywords: Road Safety; Commercial Drivers; Road Accidents; Traffic Rules